Bullying Prevention Education for Students of Kepanjen 2 State Elementary School, Jombang Regency - Rahayu Prasetiyo; Novita Nur Synthiawati; Arsika Yunarta (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The world of education is currently faced with a serious problem that befalls students, namely bullying which certainly has a negative impact on students. This act of bullying harms the victim to affect his psyche which causes the perpetrator to act arbitrarily on the victim. Perpetrators who commit these acts can adversely affect the physical and mental health of their victims. The impact that occurs on victims can trigger depression, stress, mental health disorders, to trigger anger levels to the most fatal of bullying cases is suicide. The purpose of this activity is so that school residents in general and students in particular know the types, dangers and prevention of bullying. The method used is training that uses a participatory model. Emphasis on discussions, lectures and Q&A. The results achieved are: (1) the partner understands the meaning, type, causes and punishment of bullying; (2) partners understand their strategic role in preventing bullying; and (3) partners skilled in educating students to prevent bullying from themselves. These results provide opportunities for more opportunities for teachers' strategic role in helping to prevent bullying in schools.